The role of risk management orientation and the planning function of budgeting in enhancing organizational resilience and its effect on competitive advantages during times of crises - Julia Eichholz; Nicole Hoffmann; Anja Schwering (Journal of Management Control, 2024)
Global economic crises can have a significant impact on businesses across different sectors, often leading to difficulties or even insolvency. In such a situation, organizational resilience is often considered a means to ensure the competitive advantage. Although the concept has gained popularity in recent years, empirical research on the determinants and effects of organizational resilience remains scarce. Therefore, we first examine the potential management accounting determinants of organizational resilience. Second, we investigate the effect of organizational resilience on competitive advantage. A cross-sectional survey conducted in January and February 2021 resulted in 127 observations of medium- and large-sized German companies. We find that a risk management orientation and the importance of the planning function of budgeting are positively associated with both the adaptive capability factor and the planning factor of organizational resilience. Furthermore, we find that adaptive capability increases a company's competitive advantage in both business-as-usual situations and in times of crisis. Our findings inform practitioners about how key management accounting concepts, such as risk management and corporate planning, can increase organizational resilience and, consequently, the positive outcomes of organizational resilience.
Keywords: M41; 330; Competitive advantage; Corporate planning; Crisis; Organizational resilience; Risk management